Economic burden of antimicrobial resistance and inappropriate empiric treatment in Thailand - Thitima Kongnakorn; Eszter Tichy; Kirati Kengkla; Nuttawan Kanokwanvimol; Pichaya Suthipinijtham; Chanyapat Phuripakathorn; Amer Al Taie (Cambridge University Press, 2023)
Abstract Objective: To quantify the economic burden of bacterial antimicrobial resistance in Thailand and estimate potential savings from improving the rate of appropriate empiric treatment, where effective coverage is provided within the first days of infection. Design: Cost-of-illness study. Methods: A cost-calculator, decision-tree model was developed using published data and records from 3 Thai hospitals for patients hospitalized with antimicrobial-resistant infections between 2015 and 2019. Direct and indirect costs of antimicrobial-resistant infections were assessed over a 5-year time horizon, with outcomes derived separately for cases having received appropriate empiric treatment versus inappropriate empiric treatment. In a real-world scenario, outcomes were estimated using actual rates of inappropriate empiric treatment, and in a hypothetical scenario, outcomes were estimated using decreased rates of inappropriate empiric treatment. Results: Over 5 years, in-hospital antimicrobial-resistant infections produced costs of approximately Thai baht (THB) 66.4 billion (USD 2.1 billion) in the real-world scenario and THB 65.8 billion (USD 2.1 billion) in the hypothetical scenario (0.9% cost savings relative to the real-world scenario). Most costs were attributable to income loss due to in-hospital mortality (real world: THB 53.7 billion [USD 1.7 billion]; 80.9% of costs; hypothetical: THB 53.2 billion [USD 1.7 billion]; 80.8% of costs) and hospitalization (real world: THB 10.3 billion [USD 330.8 million]; 15.5% of costs; hypothetical: THB 10.2 billion [USD 328.9 million]; 15.5% of costs). Conclusions: In-hospital antimicrobial-resistant infections produced a substantial economic toll in Thailand. This public health burden could be reduced with a strategy aimed at decreasing the rate of patients receiving inappropriate empiric treatment.